A layered view model for XML repositories and XML data warehouses - Chang, Elizabeth; Rajugan, R.; Dillon, Tharam S.; Feng, L. (IEEE, 2005)
The Object-Oriented (OO) conceptual models have the power in describing and modelling real-world data semantics and their inter-relationships in a form that is precise and comprehensible to users. Conversely, XML is fast emerging as the dominant standard for storing, describing and interchanging data among various Enterprises Information Systems (EIS) and databases. With software engineering placing added emphasis on MDA solutions and modelling approaches, it is important to investigate data models for EIS that are abstract enough to be utilized under the MDA paradigm, yet is adoptable in the current data engineering practice. In this paper, we demonstrate a set of language independent conceptual operators for constructing abstract views for XML. The proposed view model has conceptual and logical extensions for supporting abstract views definitions at the conceptual level.